Social innovation in health and community-driven engagement as a key strategy for addressing COVID-19 crisis challenges: insights and reflections from the multicultural society of Iran - Khazaee-Pool, Maryam; Pashaei, Tahereh; Ponnet, Koen (Frontiers in Public Health, 2023)
Background Social innovation is one of the strategies for appealing to people and encouraging social cooperation and engagement in interventions during crisis periods. In this regard, community engagement is an operative and innovative community health approach for achieving successful health outcomes. There is limited information about the role and operational impact of social innovation on community engagement during the challenges posed by the COVID-19 crisis. In this study, we aim to contribute to the understanding of innovative social strategies to attract social participation in crises such as the COVID-19 pandemic by highlighting the experience of social innovative strategies based on community-driven engagement in Iran. Methods This qualitative study was conducted in seven provinces of Iran—Mazandaran, Zanjan, Golestan, Lorestan, Tehran, Kurdistan, and Khuzestan—from 4 September 2021 to 1 March 2022. A sample of Iranians (15–71 years) was selected by purposeful and snowball sampling methods to participate in the study, and 187 semi-structured telephone interviews were conducted. Participants were recruited from three levels of the community: community leaders, healthcare providers, and laypeople. The data collection tool was an interview guide, which was designed based on a review of the literature. The data were analyzed using conventional content analysis. Exploratory analyses were performed to identify social innovative strategies based on community engagement used during the COVID-19 crisis in Iran. The interviews continued until data saturation was reached. Results Based on our findings, we distilled innovative strategies into 6 main themes and 37 categories: (1) information giving/sharing, (2) consultation, (3) involvement/collaboration, (4) health education and prevention, (5) empowering, and (6) advocacy. The results revealed that the participants were very driven to engage in the management and control of the COVID-19 crisis, even though they faced significant challenges. Conclusion The spread of the COVID-19 pandemic required social- and community-based responses. These reactions increased the possibility of fair access to health services, especially for vulnerable groups and minorities. As with other epidemics, applying the experience of the comprehensive participation of communities played an important and active role in the prevention and control of COVID-19. In this regard, giving and sharing information, consultation, involvement/collaboration, health education/prevention, empowerment, and advocacy are the most important innovative strategies that might encourage the community to perform COVID-19 crisis management and control.